Variational quantum gate optimization at the pulse level - Greenaway,S; Petiziol,F; Zhao,H; Mintert,F (SciPost Physics, 2024)
We experimentally investigate the viability of a variational quantum gate optimizationprotocol informed by the underlying physical Hamiltonian of fixed-frequency transmonqubits. Through the successful experimental optimization of two and three qubit quan-tum gates the utility of the scheme for obtaining gates based on static effective Hamilto-nians is demonstrated. The limits of such a strategy are investigated through the opti-mization of a time-dependent, Floquet-engineered gate, however parameter drift is iden-tified as a key limiting factor preventing the implementation of such a scheme which thevariational optimization protocol is unable to overcome.